CALLENGING TRADITIONAL ISLAMIC EDUCATION SYSTEM AS A STRENGTHENING OF THE INCLUSIVE EDUCATION PARADIGM IN INDONESIA - Ishari, Nurhafid; Wijayanti, Berly; Shodiq, Muhammad; Diana Islamy, Sarah Lady (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Traditional Islamic education in Indonesia is still dominated by madrasa education as formal education institutions and Islamic boarding schools as informal education, there are even non-formal Islamic education institutions such as religious teaching in Langgar and in the community. Meanwhile, the concept of inclusive Islamic education in Indonesia should use an approach that emphasizes openness, respect for diversity, and the provision of equal access to education for all levels of society, without distinguishing between ethnic background, religion, social status, or special needs. This is a challenge in itself in the traditional Islamic education system in Indonesia at this time. The concept of inclusive education is in line with the thinking of KH. Abdurrahman Wahid which focuses on inclusive Islamic education characterized by humanism and pluralism without discrimination against diversity and pluralism. The aim of this research is to explore the challenges of the concept of traditional Islamic education in the context of strengthening the inclusive Islamic education paradigm in Indonesia. This research uses a qualitative method with a phenomenological approach, namely in-depth data collection through interviews, observations, and is linked to studies of several Islamic educational institutions in Indonesia, including madrasas, Islamic boarding schools, and other religious education in society. So the implications of this research have a positive impact on the development of traditional Islamic education, especially in terms of increasing inclusiveness, strengthening moderate education, and raising awareness of the importance of adapting to changes in the Islamic education system in Indonesia. Then, this research also found quite significant challenges, such as disparities in the implementation of wasathiyah in various Islamic boarding school educational institutions, differences in the quality of educational resources, and the influence of extremist ideologies that are still trying to enter the world of education. Therefore, a more inclusive education system policy is needed to ensure that solutions are found to the challenges of the traditional Islamic education system, so that it can develop into education that is moderate, open-minded, and ready to face global challenges with a more peaceful and balanced perspective.